How can research improve logopaedic practice: an interdisciplinary approach - Dobravac, Gordana (Array, 2004)
The status of logopaedic practice is not defined exclusively by attitudes and/or competences inherent to the clinicians, but, frequently, by the educational background of the field. Namely, while in some environments logopaeditians can earn up to doctoral degree, in some others, their education is not even on the university level. Inevitably, this has an impact on clinical practice which in some instances tend to be too pragmatic and mechanic avoiding any reliance on data and/or theoretical framework. To understand the language pathology we assume that: 1. The linguistic and cross-linguistic research can increase our understanding of both the common language development and language pathology ; 2. Better understanding of linguistic features makes the development of adequate therapeutic materials easier ; 3. The understanding of language processing and the employment of new therapeutic materials significantly improve the therapy. In this poster an account of the interdisciplinary approach to the logopaedics will be given. The need for connecting scientific research and clinical work in order to improve diagnostics and therapy will be presented. Twofold orientation of our Laboratory - research and clinical work - can be viewed Petri dishes for developing language pathology practice. The poster will show various types of clinical practices and education in various countries.